PENEGAKAN HUKUM BERPERSPEKTIF GENDER PADA KASUS TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH PEREMPUAN (STUDI KASUS PERKARA LAPORAN POLISI NOMOR: LP/B/01/II/2024/SPKT/POLSEK MERGANGSAN/POLDA DIY) - Fitrianto Heri Nugroho (Fakultas Hukum Universitas Janabadra, 2025)
This study aims to determine and analyze the implementation of law enforcement against women facing the law as perpetrators of abuse and the factors that determine law enforcement carried out in the Yogyakarta Police Jurisdiction. This research is a qualitative research and includes normative and empirical legal research types. The research was conducted in the jurisdiction of the Yogyakarta City Police, Special Region of Yogyakarta. The approach to this research uses a sociological approach. The subject of the research is about law enforcement of criminal acts committed by women in the jurisdiction of the Yogyakarta City Police. Data analysis is carried out through data analysis related to the problem being studied and then clearly describes the actual situation regarding the facts and based on logical thinking. The results of the study can be concluded that law enforcement is applied equally between adult men and adult women in accordance with applicable legal provisions and laws, namely fulfilling the principle of recognizing and guaranteeing constitutional rights for men and women are balanced and equal before the law (equality before the law) without discrimination. The law enforcement process includes arrest, detention, investigation, prosecution, trial process and implementation of sentences according to trial decisions. All stages are carried out in accordance with legal provisions using the right law enforcement approach so that the protection of rights and principles of justice for women perpetrators of criminal acts is fulfilled. The differentiating factor in law enforcement for female perpetrators compared to male perpetrators is referring to the concept of gender perspective when implementing the law enforcement process to develop a more gender-sensitive justice system because women have more unstable physical and psychological abilities compared to men.